Presynaptic dopaminergic neuroimaging in REM sleep behavior disorder: A systematic review and meta-analysis. (October 2018) - Bauckneht, Matteo; Chincarini, Andrea; De Carli, Fabrizio; Terzaghi, Michele; Morbelli, Silvia; Nobili, Flavio; Arnaldi, Dario
Summary: The presence of polysomnography-confirmed REM sleep behavior disorder (RBD) is the stronger risk factor for having prodromal Parkinson disease (PD), followed by abnormal presynaptic dopaminergic radionuclide neuroimaging. Aim of the review is to conduct a meta-analysis of literature data regarding presynaptic dopaminergic neuroimaging in RBD. A literature search was conducted, resulting in 16 papers that met the inclusion criteria. Clinical and neuroimaging data were extracted. The studies are heterogeneous, especially for neuroimaging methodology. Two mathematical transformations were used to allow imaging data to be compared among studies. Tracer uptake progressively decreased from controls to idiopathic RBD and eventually PD patients with RBD at putamen level. Tracer uptake at caudate level overlapped between patients with idiopathic RBD and those with PD without RBD. These results support the hypothesis that idiopathic RBD patients are on the path to developing a synucleinopathy. The receiver operation characteristic analysis found good to excellent discrimination capability between all groups. Presynaptic dopaminergic neuroimaging may be a key feature in the stratification of subjects to be included in neuroprotective trials. However, literature data are heterogeneous. Multicentric, harmonized studies are needed to define the usefulness of presynaptic dopaminergic neuroimaging with the aim of testing neuroprotective trials for idiopathic RBD.